2017
DOI: 10.1016/j.scs.2016.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of 9 European public bus transportation systems

Abstract: The transportation sector is one of the largest sources of EU’s greenhouse gas emissions. In 2011, transportation represented approximately 25 percent of total EU’s greenhouse gas emissions. Urban mobility accounts for 40% of all CO2 emissions of road transport and up to 70% of other pollutants from transport. As, transportation and mobility play a crucial part both in urban economics and the quality of life, it is of great significance to ensure a low carbon transportation sector, so as to deal with the threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 8 publications
(8 reference statements)
0
29
0
Order By: Relevance
“…Nanaki et al [43] mentioned that an efficient and flexible transport system is essential for a future of low carbon transport system. Their study also found that the differences in the levels of emissions coming from the different systems of each city depict differences in the quality and utilisation of transportation networks.…”
Section: Environmental Dimensionmentioning
confidence: 99%
“…Nanaki et al [43] mentioned that an efficient and flexible transport system is essential for a future of low carbon transport system. Their study also found that the differences in the levels of emissions coming from the different systems of each city depict differences in the quality and utilisation of transportation networks.…”
Section: Environmental Dimensionmentioning
confidence: 99%
“…It also produces environmental and health impacts. In European cities, 40% of CO2 emissions and up to 70% of other pollutants are related within the intensive use of cars [3]. Noise pollution, consumption of non-renewable resources are other environmental consequences related to the use of the car.…”
Section: Introductionmentioning
confidence: 99%
“…The intensive use of motorised vehicles causes several well-known problems, including pollution, traffic congestion, energy consumption, accidents and sedentary lifestyles [6]. In European cities, 40% of CO2 emissions and up to 70% of other pollutants are related within the intensive use of cars [3]. By 2050, the EU has the goal of cutting transport emissions to 60% below 1990 levels to make cities more sustainable and liveable [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mulley et al [22] compared the impact of greenhouse gases emissions from urban bus and rail in Australia on environment. Nanaki et al [23] compared the environmental benefits of urban public bus transportation system in nine European cities in term of air pollution emissions reductions. Matute and Chester [24] employed the cost-benefit methodology to analyze the effectiveness of reductions in greenhouse gas emissions from urban transportation infrastructure in California.…”
Section: Introductionmentioning
confidence: 99%